Kesulitan Siswa SD dalam Memahami Materi 6 Benua di Dunia : Kajian Literatur (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
Social Studies (IPS) education is crucial for providing students with the knowledge, skills, and social attitudes necessary for everyday life. However, teaching about world maps and the characteristics of continents is often challenging. Several factors, including complex materials, limited learning media, and students' inability to read maps and understand geographic symbols, contribute to many students' difficulties in understanding complex geographic concepts. This study investigated the problems students face and their causes using a systematic literature review methodology. As the study showed, students tend to memorize the names of continents and their locations without understanding the relationships and characteristics of each continent. Students are less actively engaged in the learning process due to the predominance of lectures. The results showed that students can gain a better understanding of the material by using visual media and interactive learning approaches such as biorama models. These methods provide students with opportunities to relate abstract concepts to concrete representations, which enhances their understanding. It is hoped that students will not only memorize but also understand and remember details about continents using a more innovative and contextual learning approach. This research suggests improving the quality of social studies instruction in elementary schools so that students are better prepared to learn global geography concepts and international relations at the next level.